Autoethnography as a Poetics of Worlding and a Politics of Becoming: Claudia Rankine's Citizen and Kathleen Stewart's Ordinary Affects. (April 2020) - Johnson, Jessica
This article analyzes the anthropologist Kathleen Stewart's Ordinary Affects and the poet Claudia Rankine's Citizen: An American Lyric as autoethnographies of affective encounter in which the authors stylistically fracture their positionalities such that the embodied evidence of experience becomes visceral political potential. In Ordinary Affects, Stewart uses autoethnography to conjure the intensities of affect that manifest in everyday moments and spaces of encounter, detailing disparate scenes of immanent force to provide an antidote to academic studies that render power inert as they employ totalizing systems such as "neoliberalism" to analyze its effects. Using "she" to index the difference between her first-person identity as a writer and a body that imagines and senses the political-as-becoming, Stewart invites readers to participate in a poetics of worlding during which the author does not play expert witness. In the American lyric Citizen, Claudia Rankine also splits her narrative voice and uses both "I" and "you, " while evoking affective encounters of racialization that are forces of habit and routines of violence. Her poem includes not only personal anecdote or feeling but also events and texts of popular culture, enlisting her readers to take part in a poetics of worlding and a politics of becoming through which the author bears witness to "I" through "you." In effect, Rankine and Stewart use autoethnography to resist portraying political life as bound by discursive logics of self and subjecthood.